A Survey of Datacenter and Optical Data Center Networks - Esraa Ali Abdulmahdi Abdul Mahdi; Ali Al-Askery; Adnan Hussein Ali; Safiye Ghasemi (Journal of Techniques)
The technology of reconfigurable optical networks (RONs) is growing to be a promising solution to effectively cater to the rapidly increasing traffic generated by the digital society. The present study offers an overview of the datacenter technology and optical datacenter with details of its concepts and technologies. First, the optical data center systems are described and the components that describe it are network operations. Then, we detail the specific technologies that are important to data center networks throughout wide-area networks, analyzing them deeply. Finally, we make a comprehensive between some related works with an analysis of the algorithmic challenges faced by these technologies. In addition, we examine the solutions that have been developed to address these challenges and explore the relevant systems and implementation considerations.